A New EOR Technology: Gas Alternating Gas Injection - Mohammed Alsharif Samba; Ibrahim Aldokali; Mahmoud Omran Elsharaf (Universitas Islam Riau (UIR) Press, 2019)
A new method of enhanced oil recovery has been developed and applied to a simulation using some of data from the fifth SPE paper